SOME DIFFERENTIATING FIELD CHARACTERISTICS BETWEEN THE BELAIT & LAMBIR FORMATIONS, NORTH SARAWAK. - Ramli, Mohd Syamim (2011)
Similarities between the general appearances of the Belait and Lambir Formation in the field have led to difficulties in distinguishing one from another. This differentiation is important as there is an ongoing E&P in this part of Sarawak. Selected outcrops from the northern and central Sarawak have been analyzed in the field to evaluate the difference between these Formations. Field observation suggested that there are at least eight differentiating characteristics between these Formations. In terms of sedimentary features, presence of asymmetrical ripple marks on the Belait Formation indicates a fluviatile environment whereas on the Lambir Formation, symmetrical ripple marks are much more common features. Cross-beddings on the Lambir Formation are also abundantly found but it is not encountered in the Belait Formation. Fossil burrows of Ophiomorpha Nodosa are also common in the Lambir Formation but to a lesser extend in the Belait. Flow patterns features such as mud- and/or sand-filled channels are also a characteristics of the Belait Formation. Conglomerates of the Belait Formation can be found on the southern part of Sarawak. In terms of bedding and stratigraphy, heterolithics sequences are widely encountered in the Belait Formation outcrops, but rarely in the Lambir Formations. Observations on the proportions of sand and clay in these heterolithics sequences between the two Formations suggest that the Belait Formation possess a much sandier sequence. Presence of carbonaceous shales are also common in the Belait Formation whereas massive sandstones are more often encountered in the Lambir Formation. Despite these general differentitating characteristics, distinguishing some of the outcrops are still difficult as these features may not be present in all outcrops.